2021
DOI: 10.3390/atmos12020128
|View full text |Cite
|
Sign up to set email alerts
|

Valley Winds at the Local Scale: Correcting Routine Weather Forecast Using Artificial Neural Networks

Abstract: In regions of complex topography, local flows are difficult to forecast on a routine basis, especially in stable conditions, due to the coarse resolution of operational models. The Cadarache valley (southeastern France) features this sort of complex topography. The Weather Research and Forecasting (WRF) model is run daily to forecast the weather in this region with a horizontal resolution of 3 km. Such a resolution cannot resolve all topography details of the small Cadarache valley, and therefore its local win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…WRF is routinely run in an operational forecast mode in southeast France by CEA with a horizontal resolution of 3 km. This resolution is too coarse to solve the thermally driven flows in the local valleys such as those observed during IOP07 [25]. Focusing on specific situations of KASCADE-2013, [31,36] have shown that WRF simulations with a kilometric horizontal resolution, though unable to resolve CV flows during stable conditions, are quite successful for the representation of the Durance down valley flow which develops in the lowest hundreds of meters above the ground some hours after sunset.…”
Section: Configuration Of the Numerical Simulation 241 Domain Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…WRF is routinely run in an operational forecast mode in southeast France by CEA with a horizontal resolution of 3 km. This resolution is too coarse to solve the thermally driven flows in the local valleys such as those observed during IOP07 [25]. Focusing on specific situations of KASCADE-2013, [31,36] have shown that WRF simulations with a kilometric horizontal resolution, though unable to resolve CV flows during stable conditions, are quite successful for the representation of the Durance down valley flow which develops in the lowest hundreds of meters above the ground some hours after sunset.…”
Section: Configuration Of the Numerical Simulation 241 Domain Settingsmentioning
confidence: 99%
“…Dupuy et al [24] used artificial neural networks (ANNs) in order to estimate the wind speed and direction in a small valley from routine observations representative of a larger scale. Finally, [25] extended this ANN technique to forecast the valley wind from operational weather simulations performed with a resolution which was too coarse to represent the fine-scale flows.…”
Section: Introductionmentioning
confidence: 99%
“…As a measure of network accuracy, the Mean Absolute Error (MAE) was taken [34]. The satisfactory results obtained by the authors confirmed the usefulness of this tool in weather condition prediction.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Another difficulty encountered when using MLPs for weather forecasting is because ANNs are good interpolators but poor extrapolators. The dataset used to train the ANN must, therefore, contain numerous and heterogeneous examples to cover the widest range of cases that the ANN is expected to predict [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation